THE CONCEPTUAL MODELS OF E-SERVICE QUALITY TO INCREASE COMMITMENT WAQIF - Purbasari, Lintang Titian; Ratnasari, Ririn Tri (Universitas Airlangga, 2021)
This study aims to conceptualize the relationship between e-service quality and commitment waqif through e-trust with the moderator variables of communication and religiosity. The conceptual framework was developed from social exchange theory and previous literature on commitment. Nine propositions raised in this study consist of five proposed antecedents of e-service quality, namely environment quality, promotion quality, information quality, system quality, and outcome quality. Then the communication and religiosity factors are proposed no longer as determinants of commitment but as moderators, and e-trust is offered to be a mediator variable between e-service quality and commitment waqif. Many factors can affect commitment waqif, but this study only focuses on the effect of e-service quality. With this conceptual model, it is hoped that the donation platform manager can improve the e-service quality so that donors are loyal to donate through electronic services. In addition, to ease the burden on the government in collecting cash waqf funds and reach the potential that has been set faster. Further researchers can conduct empirical studies by proving all the arguments that have been put forward, also can use other factors that can affect commitment waqif.